The determinants of government expenditures in Serbia: the application of ARDL model - Vera Mirović; Branimir Kalaš; Milica Inđić (Anali Ekonomskog fakulteta u Subotici, 2023)
Government expenditures represent one of the most important issues for policymakers both in ordinary and extraordinary circumstances.  The aim of this paper is to estimate and identify the effects of selected macroeconomic determinants on government expenditures in Serbia for the period 2002-2020. Using the ARDL technique, the empirical findings confirmed that there is a long-run relationship between gross domestic product, government revenues, inflation and population size and government expenditures for the observed period. The significant and positive effects of explanatory variables are confirmed in the long run, except for inflation whose impact is not significant in the short-run. Specifically, GDP growth, higher inflation rate, greater government revenues and population contribute to the higher government expenditures level. The obtained findings give certain directions to fiscal authorities in creating and defining optimal government expenditures level in the context of influences of chosen macroeconomic variables.